Examining characteristics of high potential employees from employees’ perspective - Juhdi, Nurita; Pa'wan, Fatimah; Hansaram, Ram Milah@Simranpreet Kaur (UniversityPublications.net, 2012)
The objective of the study was to determine the major characteristics of high potential (HIPO) employees. Three hundred and twenty nine employees participated in the study. HIPO was mainly described by three major characteristics – high performance, learning agility and leadership spirit. The data were collected using survey forms and the items were adopted from various studies that discussed HIPO traits and characteristics. The multiple linear regressions showed that the first characteristic – high performance – was significantly predicted by learning agility, leadership spirit and low turnover intention. The second HIPO characteristic – learning agility – was significantly predicted by leadership spirit, high performance, organizational engagement and job engagement. The third HIPO characteristic – leadership spirit – was significantly predicted by high performance, learning agility, increased job scope, organizational engagement, number of years in the organization, education level and higher turnover intention.